Electrical Transport and Lowered Percolation Threshold in YBa2Cu3O7−δ-Nano-YBa2ZrO5.5 Composites. (25th August 2014) - Rejith, Pullanhiyodan Puthiyaveedu; Vidya, Sukumariamma; Thomas, Jijimon Kumpukattu
Abstract : We investigated the chemical reactivity and percolation characteristics of insulating nanocrystalline YBa2 ZrO5.5 prepared by modified combustion route and the YBa2 Cu3 O7− δ superconductor composite system. Structural analysis was done by using X-ray diffraction technique, surface morphology of the samples was studied using scanning electron microscopy, and electrical transport measurements like critical transition temperatures (T c ) and self-field transport critical current (J c ) were done by using standard four-probe technique. It is found that, in YBa2 Cu3 O7− δ -nano-YBa2 ZrO5.5 composite system, the superconductor and insulator materials coexist as separate phases without any noticeable chemical reaction even after sintering at high temperatures. Furthermore, percolation threshold and critical exponent are found to beV C = 0.3, t = 1.68, andu = 2.7 . And the analysis of the current flow in the polycrystalline samples reveals weak link behavior in the majority of grain connections.